ANALISIS PENERAPAN KONSEP MERDEKA BELAJAR PADA KOMUNITAS GRIYO MAOS GUNUNG ANYAR SURABAYA - Luthfiah Vanidah; Lilik Binti Mirnawati; Meirza Nanda Faradita (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aims to analyze the application of the concept of freedom of learning in the Griyo Maos Community of Gunung Anyar Surabaya (GM) with the hope of being able to become a solution to become a freedom of learning alternative and become a means of character strengthening for the children assisted by Griyo Maos Gunung Anyar Surabaya during distance learning. This research method is qualitative with research subjects are the founders and children assisted by Griyo Maos Gunung Anyar Surabaya. This study used analytical techniques consisting of data collection, data reduction, data presentation, and conclusion drawing. Data based on the results of research conducted there are 80% of children who actively participate in activities at GM, 100% felt more creative, 70% said activities at GM affect their enthusiasm for learning, 80% felt they have a leadership spirit, 100% of GM fostered children claimed to be more confident , and 80% felt a positive impact and a heightened sense of responsibility. From the questionnaires and interviews, the results were in the form of strengthening the character of GM fostered children after participating in many activities that they conceptualized themselves at GM.